Modeling a divertor with mid-leg pumping for high-power H-mode scenarios in DIII-D considering E × B drift flows - Andreas Holm; Robert S. Wilcox; Jonathan H. Yu; Thomas D. Rognlien; Marvin E. Rensink; Filippo Scotti; Roberto Maurizio; Steve L. Allen; Wilkie Choi; Anothony W. Leonard; Morgan W. Shafer; Mathias Groth; et al. (Nuclear Materials and Energy)
Edge-plasma simulations of a baffled, long-legged divertor in DIII-D, performed using the multi-fluid code UEDGE, indicate that the position of the detachment front is constrained to the location of the pump duct along the low-field side (LFS) baffle. Simulations including magnetic and E×B drifts were performed for 12.5 MW deuterium plasmas including intrinsic carbon and seeded neon to assess the optimal location of the LFS divertor pump to create a stable detachment front between the target and the X-point. The radiation front position in the simulations, taken to be indicative of the detachment front, can be controlled between the pump and X-point in the favorable magnetic field direction for H-mode access by moving the pump duct location upstream of the target along the LFS baffle. In the unfavorable magnetic field direction, the radial Eθ×B drift flows are directed towards the pumping surface, efficiently removing the injected deuterium gas and limiting the sensitivity of the radiation front location to the gas injection rate. The role of pumping rate and drift direction on the pumping efficiency are also found to affect the divertor plasma conditions and detachment front location in UEDGE simulations.